Auto-exoticism: Cultural display at the Shanghai Expo. (March 2013) - Winter, Tim
For many postcolonial countries, articulating a sense of identity and cultural nationalism has involved negotiating those histories and identities constructed and ascribed upon them by others. Indeed, such themes have long troubled many postcolonial intellectuals and been the subject of intense debates. Shanghai Expo 2010 brought this issue into focus once again, an event where national identities were performed to an audience of 73 million. This article examines the objects and architecture of cultural nationalism in relation to questions of sovereignty and enduring colonialities for a number of Asian and African countries participating in previous world's fairs and at Shanghai. It draws on the ideas of Partha Chatterjee to interpret why they embraced a language of tradition and heritage, reproducing the same geo-cultural hierarchies familiar to the age of European empire. The author argues that, within the cultural economies of globalization today, such countries engage in a form of auto-exoticism.